Dyslipidaemia & Framingham risk score: Tools for prediction of cardiovascular diseases as public health problem - Singh, Sushil Kumar; Pant, Bhawana; Davey, Anuradha; Shukla, Arvind Kumar; Ahmad, Sartaj (Indian Journal of Community Health, 2016)
Background: According to WHO, CVD is the number one cause of death globally and an estimated 17.5 million people died from CVDs in 2012, representing 31% of all global deaths. Dyslipidaemia with other cardio-metabolic risk factors are one of the major risk factors for cardiovascular diseases. This study was under taken to assess the prevalence of cardiovascular risk factors among the urban population aged 18 to 40 years. Methodology: This cross-sectional study was done at UHTC (Multan Nagar) in Meerut district from May 2014 to June 2015. 150 study participants aged 18 to 40 years of both sexes were recruited using simple random sampling. Data was collected using WHO’s STEPS criteria and modified close ended questionnaire. Data was analysed using Statistical Package for Social Sciences (SPSS v19). Results: Overall prevalence of dyslipidaemia was, low HDL-c 58.7%, hypertriglyceridemia 36%, high TC:HDL-c ratio 24%, hypercholesterolemia 14.7% and high LDL cholesterol 8.0% & Framingham risk score of developing Coronary artery disease was 8.6% risk of 6% & above and 91.4% risk of 5% or less. Conclusion: The prevalence of two cardio-metabolic risk factors was quite high in both males and females and the association between Framingham risk score & dyslipidaemias were also statistically significant. Clearly indicating that those who were having dyslipidaemia in any form were at a higher risk of having coronary artery disease in the future.